Music and Wellbeing in Everyday Life: An Exploratory Study of Music Experience in Ghana. - Carl, Florian; Kutsidzo, Rosemond (Legon Journal of the Humanities, 2016)
In this paper we highlight the experience of music in everyday contexts in Ghana. Using the Experience Sampling Method (ESM) and semi-structured interviews, we examined how people experience and use music in everyday life in potentially beneficial ways to enhance subjective wellbeing. In contrast to previous research where music's self-regulatory role has been highlighted primarily in the context of solitary music listening, for the participants in our study music also played a crucial role as a form of social and participatory performance practice. This was particularly evident in the strong connection between music, religion and social dance.